If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 3x + -4 = 14whatisx Reorder the terms: -4 + 15x + 3x = 14whatisx Combine like terms: 15x + 3x = 18x -4 + 18x = 14whatisx Solving -4 + 18x = 14ahistwx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14ahistwx' to each side of the equation. -4 + -14ahistwx + 18x = 14ahistwx + -14ahistwx Combine like terms: 14ahistwx + -14ahistwx = 0 -4 + -14ahistwx + 18x = 0 Add '4' to each side of the equation. -4 + -14ahistwx + 4 + 18x = 0 + 4 Reorder the terms: -4 + 4 + -14ahistwx + 18x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -14ahistwx + 18x = 0 + 4 -14ahistwx + 18x = 0 + 4 Combine like terms: 0 + 4 = 4 -14ahistwx + 18x = 4 Reorder the terms: -4 + -14ahistwx + 18x = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -14ahistwx + 18x = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -7ahistwx + 9x) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -7ahistwx + 9x)' equal to zero and attempt to solve: Simplifying -2 + -7ahistwx + 9x = 0 Solving -2 + -7ahistwx + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -7ahistwx + 2 + 9x = 0 + 2 Reorder the terms: -2 + 2 + -7ahistwx + 9x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -7ahistwx + 9x = 0 + 2 -7ahistwx + 9x = 0 + 2 Combine like terms: 0 + 2 = 2 -7ahistwx + 9x = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 | | 9(x-2)=72 | | 3(2x-5)+6=4x+7 | | 4(x-3)=x-5 | | 5d+15-2d-10=11 | | 256+5546=x | | 8+3x=-4x+57 | | 4x+3(4x-6)=110 | | -3+4x=4(x-7)+25 | | -6x+8y=-22 | | -4x-1=-4-7x | | 5d+15-2d-10=10 | | 7x-4=6+6x | | 3x+6(x+8)=129 | | 4(t-3)=25 | | X-5=3(2x-1) | | 5s+4c=46 | | 3e+038= | | -7x+3=x-13 | | 5+y=2x | | -34-3x=-8x+46 | | 5x+2(5x-11)=128 | | -3+-8n=5 | | 3.5r=147 | | 4y+1=2y-8 | | 57=19 | | -18=-84x | | y=100-25x | | 3x+5(3x+9)=135 |